2015
DOI: 10.1136/bmjopen-2015-009384
|View full text |Cite
|
Sign up to set email alerts
|

Reasons and remedies for under-representation of women in medical leadership roles: a qualitative study from Australia

Abstract: ObjectiveTo elicit medical leaders’ views on reasons and remedies for the under-representation of women in medical leadership roles.DesignQualitative study using semistructured interviews with medical practitioners who work in medical leadership roles. Interviews were transcribed verbatim and transcripts were analysed using thematic analysis.SettingPublic hospitals, private healthcare providers, professional colleges and associations and government organisations in Australia.Participants30 medical practitioner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
165
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(172 citation statements)
references
References 24 publications
1
165
0
1
Order By: Relevance
“…23,24 The Canadian Council of Academies assessment identified that American and European efforts are more advanced than those in Canada and that we should look to them for potential strategies. 1 Many universities have implemented guides for search committees to use when recruiting academics.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 The Canadian Council of Academies assessment identified that American and European efforts are more advanced than those in Canada and that we should look to them for potential strategies. 1 Many universities have implemented guides for search committees to use when recruiting academics.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, the first female dean of a faculty of medicine was only appointed in 1999 [5] and there is still just one female dean of a total of 17 faculties of medicine [6]. In Australia, women make up more than half of medical graduates but only 28% of medical school deans, 29% of governing board or committee members of medical colleges, and 12.5% of chief executives of hospitals larger than 1000 beds [7]. In the United Kingdom, only two out of ten chief executives of the largest teaching hospitals are women [8].…”
Section: Introductionmentioning
confidence: 99%
“…There is overwhelming evidence to demonstrate that gender equity in medicine and medical leadership in Australia has not been achieved. Women have had gender parity in Australian medical schools for decades; however, they represent only 28% of medical deans and 12.5% of hospital chief executive officers . In February 2019, The Lancet dedicated an entire issue on advancing women in science, medicine and global health .…”
mentioning
confidence: 99%